Akibat Hukum Ketentuan Pasal 33 Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 6 Tahun 2018 - Wahyudi, Bambang Tri; Safa’at, Rachmad (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the legal force, legal conflicts, and legal consequences of the provisions of Article 33 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 6 of 2018 and the formulation that was appropriate with the regulations of the payment procedures for income tax (PPh) and acquisition duty of right on land and building (BPHTB). This study used a normative juridical method with a conceptual and statute approach. Based on academic juridical perspective, article 33 Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 6 of 2018 had weak legal force, while from a formal juridical perspective the regulation remained valid before a decision to cancel its application from the Supreme Court. The provisions of Article 33 of the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 6 of 2018 contradicted the provisions of Articles 3 and 7 of Government Regulation Number 34 of 2018 and Articles 90 and 91 of Law Number 28 of 2009. It caused legal consequences i.e. legal uncertainty, legal injustice, and did not fulfill the legal force of land rights certificates as a strong means of proof. The formulation of the right regulation regarding the procedure for paying income tax and fees for acquiring land and building rights was carried out by establishing and stipulating a ministerial regulation as a normative guideline for a complete systematic land registration program.